(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
God is the infinite source of knowledge and periodically reveals tiny portions of His knowledge through chosen messengers, for good of mankind. Words revealed are perfectly designed and some content are identical and some different, as per need of mankind. These revelations are shared orally by messenger with masses and in due course of time, collected, edited and released in written form as scripture. Due to gap of time and communication issues, unintentionally, some errors and contradictions, within and between scriptures, have crept in, otherwise scriptures are in truth. There are three major religions, namely Christianity, Islam, and Hinduism, and their respective scriptures are; Bible, Quran, and Veda. Since source of all scriptures is one and the same, all scriptures are complementary and in true sense have Oneness. This oneness is proved through remarkable similarities between these scriptures by examining events such as the flood, creation of man and woman, the Last Day, and commonalities of popular names like Ram. Attributes of God described in all Scriptures are identical, namely; GOD is Eternal, Unborn, Immortal, Creator of Universe(s) and everything that exists within a Universe, Omnipotent, Omnipresent, Omniscient, Subtlest of all, Unchangeable, Unique, Always Works, Source of Eternal Bliss, etc., establishing oneness of scriptures and oneness of God.